2011
DOI: 10.1089/hum.2011.041
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Tumor-Selective Radioiodine Therapy of Liver Cancer After Systemic Nonviral Delivery of the Sodium Iodide Symporter Gene

Abstract: We reported the induction of tumor-selective iodide uptake and therapeutic efficacy of (131)I in a hepatocellular carcinoma (HCC) xenograft mouse model, using novel polyplexes based on linear polyethylenimine (LPEI), shielded by polyethylene glycol (PEG), and coupled with the epidermal growth factor receptor-specific peptide GE11 (LPEI-PEG-GE11). The aim of the current study in the same HCC model was to evaluate the potential of biodegradable nanoparticle vectors based on pseudodendritic oligoamines (G2-HD-OEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 59 publications
0
43
0
Order By: Relevance
“…**P # 0.01. application of radioiodine (13). Our previous work convincingly demonstrated the proof of principle of the NIS gene therapy concept (3,8,9,11,12,14,15). The next step toward clinical application has to be the development of gene-transfer vehicles that are able to promote targeted and efficient systemic NIS gene transfer with the potential to reach tumor metastases.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…**P # 0.01. application of radioiodine (13). Our previous work convincingly demonstrated the proof of principle of the NIS gene therapy concept (3,8,9,11,12,14,15). The next step toward clinical application has to be the development of gene-transfer vehicles that are able to promote targeted and efficient systemic NIS gene transfer with the potential to reach tumor metastases.…”
Section: Discussionmentioning
confidence: 81%
“…The enhanced permeability and retention effect is a phenomenon that describes the passive accumulation of macromolecules within the tumor stroma due to leaky tumor vasculature combined with inadequate lymphatic drainage (15) and is the basis for the observed passive tumor-targeting of dendrimer-coated adenovirus vectors after systemic delivery. Our dual-targeting strategy was further enhanced by an active transcriptional tumor-targeting using the alpha feroprotein promoter for tumor-selective replication and NIS expression.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown the potential of NIS as a reporter gene for molecular imaging with a broad range of possible applications [13,14,15,16,17,18,19,20,21,22,23,24]. In our previous work, the role of NIS as a reporter gene allowed noninvasive multimodal imaging of functional NIS expression by 99m Tc or 123 I scintigraphy as well as SPECT and 124 I PET imaging that correlated well with the results of ex vivo gamma counter measurements as well as NIS mRNA and protein analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugation of GE11 to polyethyleneimine-polyethyleneglycol (PEI-PEG-GE11, PPGE11) enabled the targeting of EGFR over-expressing tumors in vitro and in vivo (9,10). We have recently shown that local and systemic application of EGFR-targeted poly Inosine/Cytosine (PolyIC) by PEI-PEG-EGF (PP-EGF) eradicates several pre-established EGFR-over-expressing tumor models (2,3).…”
Section: Introductionmentioning
confidence: 99%